2013
DOI: 10.1080/14616696.2012.692807
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Relation Between Political Trust and Forms of Political Participation in Europe

Abstract: In the literature, two competing claims can be found on the relationship between political trust and political participation. While some authors argue that trust is a prerequisite for any form of participation to occur, others claim that distrust can be a motivating factor for participation in non-institutionalised forms of participation. The social movement literature suggests that political trust will only have these behavioural consequences if it is associated with sufficiently high levels of political effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
235
5
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(272 citation statements)
references
References 43 publications
14
235
5
18
Order By: Relevance
“…However, the effect of social capital on political participation was not found to be commensurate with early studies in Africa which revealed that social capital has an asymmetric effect on other aspects of political engagements such as; political trust, governmental effectiveness, political violence, post-conflict reconstruction and success in business. The results of our study are in agreement with the findings of recent, similar studies in developed democracies that social capital has a positive effect on political participation (Hooghe & Marien, 2013;LeRoux & Krawczyk, 2014). …”
Section: )supporting
confidence: 83%
See 1 more Smart Citation
“…However, the effect of social capital on political participation was not found to be commensurate with early studies in Africa which revealed that social capital has an asymmetric effect on other aspects of political engagements such as; political trust, governmental effectiveness, political violence, post-conflict reconstruction and success in business. The results of our study are in agreement with the findings of recent, similar studies in developed democracies that social capital has a positive effect on political participation (Hooghe & Marien, 2013;LeRoux & Krawczyk, 2014). …”
Section: )supporting
confidence: 83%
“…Most recent studies have shown this relationship to hold in most developed democracies including the United States of America (USA), Western Europe and Great Britain (Moyser & Parry, 1997;Stolle, 1998;Stolle & Rochon, 2016). For an analysis of this relationship in other European countries, see Hooghe & Marien (2013).…”
Section: Regional Evidencementioning
confidence: 99%
“…The final version can be found at: http://etn.sagepub.com/content/early/2016/07/12/1468796816656674.full.pdf+html The DOI is 10.1177/1468796816656674. 7 participation, where institutional participation is low among those with distrustful attitudes, and both high and low levels of efficacy (Hooghe & Marien, 2012).…”
mentioning
confidence: 99%
“…La investigación acerca de la participación es un fenómeno multifacético (Teney and Hanquinet, 2012). El compromiso político está actualmente divido en varios tipos: "participación convencional" versus "participación no convencional" (Contreras-Ibáñez et al, 2005;Delfino et al, 2007;Goldstone, 2003;Heaney and Rhodas, 2006;Maravall, 1981;McFarland and Thomas, 1996;Milbrath, 1965);individual "institucionalizada" versus "no-insitucionalizada" Ganuza and Francés, 2008;Hooghe and Marien 2013); o online versus offline (Dahlgren, 2011;Gibson and Cantijoch, 2013;Kim et al, 2016;Resina de la Fuente, 2010;Visers, 2014;Zarzuri, 2005). Sin embargo, no hay consenso teórico sobre estas categorías que actualmente están cambiando.…”
Section: Introductionunclassified